1980
DOI: 10.1073/pnas.77.10.6147
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hepatitis in chimpanzee carriers of hepatitis B virus: morphologic, immunologic, and viral DNA studies.

Abstract: Years after infection with hepatitis B virus, chimpanzees may have manifestations of the carrier state as described in man. In addition to serologic evidence for persistent viral infection, percutaneous liver biopsy specimens showed hepatitis B virus surface antigen in the cytoplasm and hepatitis B virus core antigen in the nucleus. Four (3,4). Recently, two distinct types of experimental hepatitis B have been described in chimpanzees, one with rapid resolution and the other with smoldering features charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 20 publications
(14 reference statements)
2
20
0
Order By: Relevance
“…The presence of slowly migrating closed circular DNA in human livers infected with HBV has been observed (13). The pattern of electrophoretic migration of DNA bands seen in the present study may be comparable to the pattern reported for liver and pancreatic tissues infected with DHBV (10 (14) by digestion with Bgl II endonuclease.…”
supporting
confidence: 75%
“…The presence of slowly migrating closed circular DNA in human livers infected with HBV has been observed (13). The pattern of electrophoretic migration of DNA bands seen in the present study may be comparable to the pattern reported for liver and pancreatic tissues infected with DHBV (10 (14) by digestion with Bgl II endonuclease.…”
supporting
confidence: 75%
“…3). The data for the 10 12 vg group are shown in Fig. 3, but similar results were obtained in all groups.…”
Section: Construction Of Trans-splicing Aav Vectorssupporting
confidence: 62%
“…Chimpanzees are susceptible to HBV infection, but only develop a mild liver inflammatory reaction (10), and their use in laboratory research is further limited because of ethical and financial considerations. Studies of HBV-related viruses in woodchucks, ground squirrels and ducks have improved our knowledge of HBV virology and the development of antiviral agents, but have not led to a better understanding of HBV immunopathology (11).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are important biomedical (as well as obvious morphological and cognitive) differences between the two species, which thus far have eluded any molecular explanation within this supposedly 1% diversity range. Among these are our differential handling of a number of infectious agents, e.g., HIV (progression to AIDS) (4), late complications of hepatitis B and C (5,6), as well as susceptibility to Plasmodium falciparum (7), which are of utmost public health importance. The molecular basis of these distinctive traits is thought to be in large part encoded within the MHC, where MHC class I molecules sample pathogen-derived antigenic peptides for recognition by the CD8 ϩ ␣␤ T cell receptor expressing cytotoxic T cells (8).…”
mentioning
confidence: 99%